Chemical failure analysis of artificial lift system in petroleum industry: A review (2018)
In the following research described the chemical agents which affect the artificial lift functioning it was based on a bibliographical review of scientific articles and documents that they specialize in an artificial lift system. We describe the modification caused by the different agent in the equipment in order to offer to the reader a synthesis of the biggest causers of rod failure in the artificial lift systems.